Efektivitas Wordwall dalam Evaluasi PAI di SDN 26 Rimbo Kaluang - Wilda Apriliani; Remiswal Remiswal; Khadijah Khadijah (Lembaga Yasin AlSys, 2025)
This study originated from the problem of PAI evaluation tools that are less interactive and boring at State Elementary School (SDN) 26 Rimbo Kaluang Padang, which can reduce student motivation and learning achievement. This study aims to examine the effectiveness of the Wordwall interactive game platform as an evaluation tool in PAI learning at SDN 26 Rimbo Kaluang Padang. This study used quasi-experiment with Non-Equivalent Control Group design. The experimental class was assessed using the Wordwall tool, while the control class was assessed using a conventional test. was assessed using conventional tests. The results showed that there was a significant effect on both classes after treatment, and the average value of the experimental class was 74.16> control class 65.8. Independent t-test concluded that learning PAI using Wordwall is more efficient than conventional tests. From the practical side, this study proposes to PAI teachers and elementary schools to utilize Wordwall as an alternative evaluation tool. From the theoretical side, this study increases the insight into the efficiency of using Wordwall. Game-based learning to measure the understanding of religious materials. This study aims to find the most efficient type of Wordwall activity for various PAI subjects and its contribution to the affective side of students.